Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Prove that $$\int_0^{\infty} \frac{\sin(2013 x)}{x(\cos x+\cosh x)}dx=\frac{\pi}{4}$$

share|cite|improve this question
1. The integrand is even. 2. Use Parseval's Theorem. – Ron Gordon Feb 1 '13 at 21:12
@rlgordonma: good point. I'll check this way! Thanks! – user 1618033 Feb 1 '13 at 21:14
And yes, it is more properly called Plancherel's Theorem. But many people (like my Optics colleagues) just call it Parseval's theorem all the same. – Ron Gordon Feb 1 '13 at 21:29
@rlgordonma Thank you for the link. Ah! Plancherel, this I know. I see, Wikipedia confirms that it is often called Parseval in other domains of science and engineering fields. – 1015 Feb 1 '13 at 21:33
@Chris'ssister: Nice question, as always. +1 – Babak S. Feb 7 '13 at 11:35
up vote 21 down vote accepted

Because the integrand is even, contour integration yields $$ \begin{align} &\int_0^\infty\frac{\sin(mx)}{x(\cos(x)+\cosh(x))}\mathrm{d}x\\ &=\frac12\int_{-\infty}^\infty\frac{\sin(mx)}{x(\cos(x)+\cosh(x))}\mathrm{d}x\\ &=\frac12\int_{-\infty-i}^{\infty-i}\frac{\sin(mx)}{x(\cos(x)+\cosh(x))}\mathrm{d}x\\ &=\frac1{4i}\int_{\gamma^+}\frac{e^{imz}}{z(\cos(z)+\cosh(z))}\mathrm{d}z -\frac1{4i}\int_{\gamma^-}\frac{e^{-imz}}{z(\cos(z)+\cosh(z))}\mathrm{d}z\\ &=\frac{2\pi i}{4i}\frac12 +2\frac{2\pi i}{4i}\sum_{k=0}^\infty(-1)^{k+1}\frac{\mathrm{sech}\left(\frac{2k+1}{2}\pi\right)}{\frac{2k+1}{2}\pi}\frac{\cos\left(m\frac{2k+1}{2}\pi\right)}{\exp\left(m\frac{2k+1}{2}\pi\right)}\\ &=\frac\pi4+\pi\sum_{k=0}^\infty(-1)^{k+1}\frac{\mathrm{sech}\left(\frac{2k+1}{2}\pi\right)}{\frac{2k+1}{2}\pi}\frac{\cos\left(m\frac{2k+1}{2}\pi\right)}{\exp\left(m\frac{2k+1}{2}\pi\right)}\\ &=\frac\pi4\qquad\text{for odd $m$} \end{align} $$ where $\gamma^+$ goes from $-R-i$ to $+R-i$ then circles counterclockwise back in the upper half plane along $|z+i|=R$ and $\gamma^+$ goes from $-R-i$ to $+R-i$ then circles clockwise back in the lower half plane along $|z+i|=R$.

The residue of $f(z)=\dfrac{e^{imz}}{z(\cos(z)+\cosh(z))}$ at $z=0$ is $\frac12$.

Let $\alpha=\frac{1+i}{2}$. As noted in this answer, $f$ has singularities at $\pm(2k+1)\pi\alpha$ and $\pm(2k+1)\pi\overline{\alpha}$.

The sum of the residues in the upper half plane at $(2k+1)\pi\alpha$ and $-(2k+1)\pi\overline{\alpha}$ is the same as the sum of the residues in the lower half plane at $(2k+1)\pi\overline{\alpha}$ and $-(2k+1)\pi\alpha$. Both are equal to $$ (-1)^{k+1}\frac{\mathrm{sech}\left(\frac{2k+1}{2}\pi\right)}{\frac{2k+1}{2}\pi}\frac{\cos\left(m\frac{2k+1}{2}\pi\right)}{\exp\left(m\frac{2k+1}{2}\pi\right)} $$ Note that for odd $m$, these are all $0$; $x=m\frac{2k+1}{2}\pi\equiv\frac\pi2\pmod{\pi}\Rightarrow\cos(x)=0$. This is not so for even $m$. Thus, $$ \int_0^\infty\frac{\sin(2013x)}{x(\cos(x)+\cosh(x))}\mathrm{d}x=\frac\pi4 $$

share|cite|improve this answer
Yeah, it seems that the complex analysis makes miracles. Very nice. (+1) – user 1618033 Feb 25 '13 at 20:44
@Chris'ssisterandpals: I first looked to see if the function was even so that I could extend the domain of integration to $(-\infty,+\infty)$ in order to use contour integration. – robjohn Feb 25 '13 at 21:05
@Chris'ssisterandpals: Not to be picky, but my name is Rob :-) thanks for the bounty, arrrgh! – robjohn Feb 25 '13 at 21:13
OK! Welcome. :-) – user 1618033 Feb 25 '13 at 21:24
@Chris'ssisterandpals: I am trying this integral in Mathematica, and it is taking a long time. – robjohn Feb 25 '13 at 21:35

Consider a general case:

$$I(m)=\int_0^{\infty} \frac{\sin(m x)}{x(\cos x+\cosh x)}dx$$ where $m$ is a positive integer.

At first, let's try with m=1

$$I(1)=\int_0^{\infty} \frac{\sin x}{x(\cos x+\cosh x)}dx$$ As a first step we note that

$$\frac{\sin x}{\cos x+\cosh x}=-2\sum_{k=1}^{\infty}(-1)^ke^{-xk}\sin(xk)$$ This relationship can be derived from the following geometric series sum:
$$\sum_{k=1}^{\infty}(-1)^ke^{-xk}e^{ixk}=-\frac{e^{-x}e^{ix}}{1+e^{-x}e^{ix}}$$ Imaginary part of this gives the relationship above. Thus, the integral:

$$I(1)=-2\sum_{k=1}^{\infty}(-1)^k\int_{0}^{\infty}e^{-xk}\sin(xk)\frac{dx}{x}$$ But

$$\int_{0}^{\infty}e^{-xk}\sin(xk)\frac{dx}{x}=\frac{\pi}{4}$$ This result follows from the well known integral

$$\int_{0}^{\infty}e^{-xa}\sin(xk)dx=\frac{k}{a^2+k^2}$$ if we integrate the last with respect to $a$ from $a=k$ to $a=\infty$. We get:

$$I(1)=-2\sum_{k=1}^{\infty}(-1)^k\frac{\pi}{4}=\frac{\pi}{2}\sum_{k=1}^{\infty}(-1)^{k-1}$$ The sum

$$\sum_{k=1}^{\infty}(-1)^{k-1}=1-1+1-1+...=\frac{1}{2}$$ was already known in the times of Leibniz.


$$I(1)=\frac{\pi}{4}$$ But even in the next case of $m=2$ i have no clue, how to evaluate the integral. Numerical calculations suggest that the result holds for every $m$ including $m=2013$

share|cite|improve this answer
@Mercy $\frac{1}{1+x}=1-x+x^2-x^3+...$ – Martin Gales Feb 20 '13 at 15:31
@Mercy $\lim_{x\to1-0}(1-x+x^2-x^3+...)=\lim_{x\to1-0}\frac{1}{1+x}=\frac{1}{2}$. I am not saying that the sum converges to $\frac{1}{2}$. I am saying that the sum is equal to $\frac{1}{2}$. – Martin Gales Feb 21 '13 at 6:14
@Mercy Look at Cesàro summation on Wikipedia. – Martin Gales Feb 23 '13 at 8:35
@MartinGales I think you are mixing things up, it is clear that the series $\sum_{k=1}^\infty(-1)^{k-1}$ does not converge, and I'm surprised you still believe it does. In fact, a necessary condition for the convergence of a series $\sum_{k=1}^\infty a_k$ is that $a_k \to 0$ which obviously is not satisfied. – Mercy King Feb 23 '13 at 18:58
@MartinGales I'm affraid I have to agree with Mercy, I don't see why the series $\sum_{k=1}^\infty(-1)^{k-1}$ should be convergent since the limit $\lim_{k \to \infty}(-1)^{k-1}$ is not zero. – albmiz-mth Feb 24 '13 at 22:37

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{\int_{0}^{\infty}{\sin\pars{2013 x}\,\dd x \over x\bracks{\cos\pars{x} + \cosh\pars{ x}}}={\pi \over 4}:\ {\large ?}}$

Note that \begin{align}&\color{#c00000}{\cos\pars{x} + \cosh\pars{x}} =\cos\pars{x} + \cos\pars{x\ic} \\[3mm]&=\cos\pars{{x + x\ic \over 2} + {x - x\ic \over 2}} +\cos\pars{{x + x\ic \over 2} - {x - x\ic \over 2}} =2\cos\pars{x + x\ic \over 2}\cos\pars{x - x\ic \over 2} \\[3mm]&=2\cos\pars{\mu x}\cos\pars{\mu^{*}x} \qquad\mbox{where}\qquad\mu\equiv{1 + \ic \over 2} = \expo{\pi\ic/4} \end{align}

Then, \begin{align}&\color{#c00000}{% \int_{0}^{\infty}{\sin\pars{m x}\,\dd x \over x\bracks{\cos\pars{x} + \cosh\pars{ x}}}} ={1 \over 4}\int_{-\infty}^{\infty} {\sin\pars{mx} \over x\cos\pars{\mu x}\cos\pars{\mu^{*}x}}\,\dd x\end{align} With the identity $\ds{{\sin\pars{\xi} \over \xi} = \int_{0}^{1}\cos\pars{k\xi}\,\dd k =\Re\int_{0}^{1}\expo{\ic\verts{k}\xi}\,\dd k}$ we'll have: $$ \color{#c00000}{% \int_{0}^{\infty}{\sin\pars{m x}\,\dd x \over x\bracks{\cos\pars{x} + \cosh\pars{ x}}}} ={1 \over 4}\,m\,\Re\int_{0}^{1}\color{#00f}{\int_{-\infty}^{\infty} {\expo{\ic\verts{mk}x}\,\dd x \over \cos\pars{\mu x}\cos\pars{\mu^{*}x}}}\,\dd k \tag{1} $$

Zeros of $\ds{\cos\pars{\mu x}}$ are given by $\ds{\pars{~\mbox{with}\ n \in {\mathbb Z}~}}$: $$ x_{n} = \pars{n + \half}\,{\pi \over \mu} =\pars{2n + 1}\,\pars{1 - \ic}\,{\pi \over 2}\,,\qquad \Im\pars{x_{n}} > 0\quad\mbox{if}\quad n=-1,-2,-3,\ldots $$ Similarly, zeros of $\ds{\cos\pars{\mu^{*}x}}$ are given by $\ds{\pars{~\mbox{with}\ n \in {\mathbb Z}~}}$: $$ x_{n}^{*} = \pars{n + \half}\,{\pi \over \mu^{*}} =\pars{2n + 1}\,\pars{1 + \ic}\,{\pi \over 2}\,,\qquad \Im\pars{x_{n}^{*}} > 0\quad\mbox{if}\quad n=0,1,2,\ldots $$ $\large\begin{array}{|c|}\hline \mbox{Note that}\quad \ds{x_{-n - 1} = -x_{n}}\\ \hline\end{array}$.

Then, \begin{align}&\color{#00f}{\int_{-\infty}^{\infty} {\expo{\ic\verts{mk}x}\,\dd x \over \cos\pars{\mu x}\cos\pars{\mu^{*}x}}} \\[3mm]&=2\pi\ic\bracks{% \sum_{n = -\infty}^{-1} {\expo{\ic\verts{mk}x_{n}} \over -\mu\sin\pars{\mu x_{n}}\cos\pars{\mu^{*}x_{n}}} + \sum_{n = 0}^{\infty} {\expo{\ic\verts{mk}x_{n}*}\over \cos\pars{\mu x_{n}^{*}}\pars{-\mu*}\sin\pars{\mu^{*}x_{n}^{*}}}} \\[3mm]&=2\pi\ic\sum_{n = 0}^{\infty}\bracks{% {\expo{-\ic\verts{mk}x_{n}} \over \mu\sin\pars{\mu x_{n}}\cos\pars{\mu^{*}x_{n}}} - {\expo{\ic\verts{mk}x_{n}*}\over \mu^{*}\sin\pars{\mu^{*}x_{n}^{*}}\cos\pars{\mu x_{n}^{*}}}} \\[3mm]&=-4\pi\,\Im \sum_{n = 0}^{\infty}{\mu^{*} \over \verts{\mu}^{2}}\, {\expo{-\ic\verts{mk}x_{n}} \over \sin\pars{\mu x_{n}}\cos\pars{\mu^{*}x_{n}}} \\[3mm]&=-4\pi\,\Im \sum_{n = 0}^{\infty}{\pars{1 - \ic}/2 \over 1/2}\, {\expo{-\ic\verts{mk}x_{n}}\over \sin\pars{\bracks{2n + 1}\pi/2}\cos\pars{\ic\bracks{2n + 1}\pi/2}} \end{align}

$$\color{#00f}{\int_{-\infty}^{\infty} {\expo{\ic\verts{mk}x}\,\dd x \over \cos\pars{\mu x}\cos\pars{\mu^{*}x}}} =-4\pi\,\Im \sum_{n = 0}^{\infty}{\pars{-1}^{n} \over \cosh\pars{\bracks{2n + 1}\pi/2}}\, \pars{1 - \ic}\expo{-\ic\verts{mk}x_{n}} $$

We replace this result in expression $\pars{1}$: \begin{align}&\color{#c00000}{% \int_{0}^{\infty}{\sin\pars{m x}\,\dd x \over x\bracks{\cos\pars{x} + \cosh\pars{ x}}}} =-\pi\,m\,\Im \sum_{n = 0}^{\infty}{\pars{-1}^{n} \over \cosh\pars{\bracks{2n + 1}\pi/2}}\, \pars{1 - \ic}\int_{0}^{1}\expo{-\ic\verts{m}x_{n}k}\,\dd k \\[3mm]&=-\pi\,m\,\Im \sum_{n = 0}^{\infty}{\pars{-1}^{n} \over \cosh\pars{\bracks{2n + 1}\pi/2}}\, \pars{1 - \ic}\,{\expo{-\ic\verts{m}x_{n}} - 1 \over -\ic\verts{m}x_{n}} \\[3mm]&=-\pi \sgn\pars{m}\Im \sum_{n = 0}^{\infty}{\pars{-1}^{n} \over \cosh\pars{\bracks{2n + 1}\pi/2}}\, \,\ic\,{\expo{-\ic\verts{m}\pars{2n + 1}\pi/2} \expo{-\verts{m}\pars{2n + 1}\pi/2} - 1 \over \pars{2n + 1}\pi/2} \\[3mm]&=-2\sgn\pars{m}\sum_{n = 0}^{\infty}{\pars{-1}^{n}\over \pars{2n + 1}\cosh\pars{\bracks{2n + 1}\pi/2}}\times \\[3mm]& \phantom{=-2\sgn\pars{m}\sum_{n = 0}^{\infty}} \bracks{\cos\pars{\verts{m}\pars{2n + 1}\,{\pi \over 2}} \expo{-\verts{m}\pars{2n + 1}\pi/2} - 1} \end{align}

Note that $$ 2\sum_{n = 0}^{\infty}{\pars{-1}^{n}\over \pars{2n + 1}\cosh\pars{\bracks{2n + 1}\pi/2}} = {\pi \over 4} $$

\begin{align}&\color{#00f}{\large% \int_{0}^{\infty}{\sin\pars{m x}\,\dd x \over x\bracks{\cos\pars{x} + \cosh\pars{ x}}}}= \\[3mm]&\color{#c00000}{\left\lbrace\begin{array}{lcl} {\pi \over 4}\,\sgn\pars{m} & \mbox{if} & m\ \mbox{is odd} \\[3mm]\sgn\pars{m}\braces{% {\pi \over 4} -2\pars{-1}^{\verts{m}/2}\sum_{n = 0}^{\infty}\pars{-1}^{n}\, {\expo{-\verts{m}\pars{2n + 1}\pi/2}\over \pars{2n + 1}\cosh\pars{\bracks{2n + 1}\pi/2}}} & \mbox{if} & m\ \mbox{is even} \end{array}\right.} \end{align}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.